Salud mental de los médicos generales colombianos durante la pandemia: reflexiones de una breve encuesta - Martínez Miranda, Mayra Alejandra; Wilches Visbal, Jorge Homero (Hacia la Promoción de la Salud, 2021)
Since before the COVID-19 pandemic, the fact that physicians and other health professionals are subjected to different states of emotional and physical fatigue associated with their work has been known (1). Recent studies have found a significant incidence of depression in this population compared to others, but this reality has been insufficiently addressed by state agencies (2). In the context of a pandemic, a greater emotional impact on health workers is predictable due to the stress of this unprecedented situation. Once this thesis is verified, the need to address the underlying risks that health personnel have regarding the development of various mental health problems associated with anxiety, depression or suicide is raised by means of efficient preventive measures that stipulate protocols aimed at improving the work environment (2).